Distributed spectral conjugate gradient algorithm for node localization in wireless sensor networks - Jiang, Junzheng; Liu, Xinyi; Zhou, Fang (Digital signal processing, 2025)
Node localization is a key problem in wireless sensor networks (WSNs). Most existing centralized algorithms require processing data from the entire graph at each operation, leading to high computational load and making scalability difficult as the graph size increases. In this paper, a novel distributed spectral conjugate gradient (DSCG) algorithm is proposed to solve the original optimization problem directly, in which the gradient vector and step-size are approximately calculated via a distributed manner in each iteration. The approximation calculation is based on decomposition of graph capturing the WSNs structure. The proposed algorithm can improve scalability while maintaining good localization accuracy. Experimental results verify the effectiveness of the proposed algorithm.